2020
DOI: 10.1523/eneuro.0130-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Circuit Structure on Odor Representation in the Insect Olfactory System

Abstract: In neuroscience, the structure of a circuit has often been used to intuit function-an inversion of Louis Kahn's famous dictum, "Form follows function" (Kristan and Katz, 2006). However, different brain networks may use different network architectures to solve the same problem. The olfactory circuits of two insects, the locust, Schistocerca americana, and the fruit fly, Drosophila melanogaster, serve the same function-to identify and discriminate odors. The neural circuitry that achieves this shows marked struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…4A). For the assessment of coding capacity, we examined the KC hamming code dimensionality, using binary representations to describe activated and inactivated states ( 45-47 ). Notably, through PCA, we found that γ KCs exhibited significantly higher coding capacity compared to α/β and α’/β’ KCs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4A). For the assessment of coding capacity, we examined the KC hamming code dimensionality, using binary representations to describe activated and inactivated states ( 45-47 ). Notably, through PCA, we found that γ KCs exhibited significantly higher coding capacity compared to α/β and α’/β’ KCs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Modeling studies (Rajagopalan and Assisi, 2020) have also found that the categorization of odors in the MB depends on changes in PN responses caused by conditioning. Our study suggests a potential mechanism for this change in KC responses.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, odor presentations without any reinforcement weaken their representation in KCs [61]. Modeling studies [62] have also indicated that the categorization of odors in the MB depends on changes in PN responses caused by conditioning. Our study suggests a potential mechanism for this change in KC responses.…”
Section: Discussionmentioning
confidence: 99%
“…Beginning with Marr-Albus theory of the cerebellum in the 1970’s, expansion coding has been hypothesized to perform pattern separation. The ratio between sensory channels and expansion layer neurons, and the number of sensory inputs that individual expansion layer neurons receive, are theorized to be key parameters in balancing perception, discrimination, and generalization (Albus, 1971; Babadi and Sompolinsky, 2014; Cayco-Gajic and Silver, 2019; Hiratani and Latham, 2022; Ito, 1972; Jefferis et al, 2007; Jortner et al, 2007; Litwin-Kumar et al, 2017; Luo et al, 2010; Marr, 1969; Modi et al, 2020; Rajagopalan and Assisi, 2020). However, the perceptual and behavioral effects of altering hard-wired quantitative relationships have not been experimentally tested.…”
Section: Introductionmentioning
confidence: 99%